Novel Scalable Topologies of High Power Density Quadratic Converters With Low Voltage Stress on Power Diode - Md Samiullah; Mohammed A. Al. Hitmi; Atif Iqbal; Shirazul Islam (IEEE Open Journal of the Industrial Electronics Society)
High-gain dc–dc converters are used for a number of applications including the power processing of several low-voltage renewable energy sources (solar photovoltaic and fuel cells) while they are integrated into a microgrid. This article introduces two novel designs of high power density nonisolated quadratic boost converters, which neither uphold the cascaded architecture nor involve coupled inductors in them. The proposed converters utilize the switched-inductors and switched-capacitor-based modules for voltage boosting. Despite having a higher output voltage, the proposed topology in its extended mode offloads the issue of high voltage stress at the devices. The output voltage can be extended to further higher levels without requiring additional circuits for peak inverse voltage (PIV) suppression at the output diode. The current at the input and output terminals are continuous, which facilitates the converter for various applications such as distributed generation (DG)s integration to microgrid and uninterruptible power supplies for integrated battery storage systems. The switched-inductor-switched-capacitor quadratic converter and its extended topology, extended switched-inductor-switched-capacitor quadratic converter, are analyzed thoroughly in different modes of conduction and the performance is justified by developing a hardware prototype ranging for a maximum power of 400 W. The switching frequency is maintained at 50 kHz.